The contribution of Saghir Akhtar in pharmaceutical science - Omar, Nurihan; Kabbashi, Nasreldin A. (IIUM Press, 2011)
The objective ofthis chapter is to study the contribution ofSaghir Akhtar in the field of pharmaceutical sciences. The significance of this chapter explores the study done by Saghir Akhtar which is beneficial to pharmaceutical field. The methodology used in doing this research is library based research and most of data is collected from a pharmaceutical journal which is from a reliable source